2019
DOI: 10.3354/cr01557
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and analysis of 1900-2017 snowfall events on the southeast coast of Spain

Abstract: In this paper, we have reconstructed and analysed snowfall events on the coast of the natural region of south-eastern Iberia (Spain) over the period 1900 to 2017. Due to the lack of continuous reliable meteorological information, we supplemented our analysis of official sources by consulting the daily newspapers for the days when snow was most likely. We selected 3 cities which are spatially representative for the study area as a whole and for which there is press coverage throughout this period. In north-sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Zhou et al revealed an increase in the frequency of heavy snowfall events, while light snowfall events in NEC decreased during 1961-2014 [14]. Furthermore, there has been other research associated with reconstruction of snowfall events in China and other regions of globe, which enhance our understanding of snowfall variability [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al revealed an increase in the frequency of heavy snowfall events, while light snowfall events in NEC decreased during 1961-2014 [14]. Furthermore, there has been other research associated with reconstruction of snowfall events in China and other regions of globe, which enhance our understanding of snowfall variability [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In some areas such as the one in our study, which considers a small portion of the Apennine chain in central Italy, no detailed or trend studies have been carried out to define a snow cover regime. Snow cover data are often subject to rather large gaps, in some cases recorded manually and only in rare cases automatically with snow measuring weather stations, so that data reconstructions are often necessary [10,11]. In addition, satellite survey data are not always reliable, both in terms of quantity and in terms of the presence or absence of the snow event, so major calibrations with weather stations are necessary, which do not always lead to acceptable results [12][13][14].…”
Section: Introduction 1aim Of the Study And State Of The Artmentioning
confidence: 99%
“…The analysis of journalistic information is one of the most interesting lines of climate research that exist, with important precedents in our country. Together with the use of documentary sources -whether ecclesiastical, municipal or private (Barriendos 1995;Martín and Barriendos 2000)-, the press has revealed to be an important way of transforming qualitative information into quantitative (Ruiz 1998;Pérez 2001;Martínez-Ibarra 2019). As J. Olcina points out, "it brings the researcher closer to the knowledge of the perception of atmospheric facts and climatic variations actually experienced by a society, oblivious to calculations of means, deviations, trends or probabilities that nature often dismantles" (Olcina, 2000).…”
Section: Introductionmentioning
confidence: 99%